Checking the sea: geographies of authority on the East Norfolk Coast (1790–1932). Issue 2 (October 2019) - Matless, David
Abstract: This article examines coastal defence in East Norfolk between the late eighteenth and early twentieth centuries. From 1802 until 1932 sea defence between Happisburgh and Winterton was the responsibility of the Commissioners of Sewers for the Eastern Hundreds of Norfolk, more commonly known as the Sea Breach Commission (SBC). This article explores the geographies of authority shaping sea defence, with the SBC a body whose relationship to the local and national state could be uneasy. The article outlines the SBC's nineteenth-century roles and routines, and examines its relationship to outside expertise, including its early hiring of geologist William Smith. The article reviews challenges to the SBC's authority following late nineteenth-century flood events, details its early twentieth-century routines, and examines disputes over development on the sandhills. The article details the SBC's dealings with an emerging national 'nature state', around issues such as coastal erosion and land drainage, matters which led to the SBC's demise following the 1930 Land Drainage Act. The article concludes by considering the SBC's contemporary resonance in a time of challenges to the role of the nature state, and anxieties over coastal defence.